Extensively drug-resistant Acinetobacter baumannii isolated in a university hospital: Role of inter-hospital transmission - Gonzalo Rivera; Juan Bulnes; Claudia Castillo; Maria Cristina Ajenjo; Patricia Garcia; Jaime Labarca (Journal of Infection in Developing Countries)
Introduction: Acinetobacter baumannii causes severe infections that primarily affect intensive care unit (ICU) patients. It has a high prevalence of multidrug resistance, including carbapenems, and a high potential for intra-hospital and inter-hospital transmission. The aim of this study was to determine the origin of extensively drug-resistant (XDR) A. baumannii isolates in our hospital during 2009. Methodology: This was an observational retrospective study. Isolates of A. baumannii were obtained from patients hospitalized during 2009. XDR isolates were defined using criteria published by Magiorakos et al.. The isolates were classified as community acquired, hospital acquired, and inter-hospital transmission. Results: A total of 48 isolates of A. baumannii were isolated during 2009, corresponding to 34 patients. Of these, 18 (53%) were susceptible, 6 (18%) were multidrug resistant (MDR), and 10 (29%) were XDR. Of the 10 XDR isolates, 9 were isolated from patients transferred from other hospitals. The median time of hospitalization in origin hospitals was 17 days, while the median time of hospitalization in the study hospital, previous to isolation of A. baumannii, was 1 day. A total of 6 out of 10 patients had a positive culture taken on the day of admission. None of the patients shared a clinical ward or time during hospitalization. Genotypic characterization demonstrated the existence of two clones (A and B) which were geographically associated with patients transferred from two different regions of the country. Conclusions: During 2009, all XDR A. baumannii isolates were recovered from patients coming from other hospitals, indicative of inter-hospital transmission.